2021
DOI: 10.1186/s12880-021-00702-4
|View full text |Cite
|
Sign up to set email alerts
|

Combination of shear wave elastography and BI-RADS in identification of solid breast masses

Abstract: Background To explore the value of quantitative shear wave elastography (SWE) plus the Breast Imaging Reporting and Data System (BI-RADS) in the identification of solid breast masses. Methods A total of 108 patients with 120 solid breast masses admitted to our hospital from January 2019 to January 2020 were enrolled in this study. The pathological examination served as the gold standard for definitive diagnosis. Both SWE and BI-RADS grading were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…This upgraded classification may be due to lesion features such as irregular shape, different sized calcifications and posterior shadowing. The low positive predictive value and the presence of false positive cases can be compensated for by combining US BI-RADS with elastography or contrast-enhanced US (13)(14)(15)(16)(17). Furthermore, given its high accuracy, cost effectiveness, low complication rate and convenience, core needle biopsy is the most common method used for impalpable and palpable lesions (18), and most suspicious lesions undergo an initial core needle biopsy first.…”
Section: Discussionmentioning
confidence: 99%
“…This upgraded classification may be due to lesion features such as irregular shape, different sized calcifications and posterior shadowing. The low positive predictive value and the presence of false positive cases can be compensated for by combining US BI-RADS with elastography or contrast-enhanced US (13)(14)(15)(16)(17). Furthermore, given its high accuracy, cost effectiveness, low complication rate and convenience, core needle biopsy is the most common method used for impalpable and palpable lesions (18), and most suspicious lesions undergo an initial core needle biopsy first.…”
Section: Discussionmentioning
confidence: 99%
“…As far as the overall study was concerned, there was no definite evidence to indicate which was better, SE or SWE ( 18 ). However, the role of SWE in the diagnosis, differentiation, efficacy evaluation and prediction of breast cancer was obvious ( 13 , 14 , 27 ). One study demonstrated the superior predictive value of Emax in combination with BI-RADS category 4a in breast cancer screening ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a multicellular study, 104 (47.1%) of 221 false-positive results were correctly diagnosed as non-breast cancer by conventional ultrasound combined with SE ( 32 ). ​A study on solid breast masses found that SWE plus conventional ultrasound BI-RADS was more valuable in distinguishing benign and malignant breast lesions than color doppler or SWE alone ( 27 ). In our research, 27.4%-61.9% of category 4a lesions could be avoided biopsy by the combination of SE and SWE, which might contain no more than 2 cases of breast cancer smaller than 1cm, and would have the chance to be saved in the follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Shear-wave elastography (SWE) is a promising elastographic technique that can provide quantitative parameters to depict tissue stiffness, increase confidence in breast lesion characterization, and provide fine intra-and inter-observer reproducibility (7)(8)(9)(10). Previous studies have shown that most malignant lesions are much stiffer than benign lesions (3,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that SWE has advantages in distinguishing benign tumors from malignant tumors, and these studies have indicated that SWE features, including mean elasticity and maximum elasticity (Emax), could improve the specificity of B-mode US from 43.1-61.0% to 65.7-87.7% without resulting in a loss of sensitivity (12)(13)(14)(15). However, the most valuable SWE feature and cutoff value have not yet been unified.…”
Section: Introductionmentioning
confidence: 99%